Reformpädagogik als eine Antwort auf die Modernisierungsprozesse am Anfang des 20. Jahrhunderts - Wolting, Monika (Glottodidactica, 2011)
After a prolonged absence of the topic of education reformers in the public discussion nowadays it’s obviously an increased interest in their approaches and models of performance. The theoretical reflections of the progressive education based on the ideas of the creative power of the child figuring in a mythical, romantic-coded image of the child as a genius. This conception was in opposite to the rigid forms of teaching, to every automatism of learning, against the authoritarian treating of teachers with students.